In Vitro Cytotoxicity Evaluation of Plastoquinone Analogues against Colorectal and Breast Cancers along with In Silico Insights - Halilibrahim Ciftci; Belgin Sever; Nilüfer Bayrak; Mahmut Yıldız; Hatice Yıldırım; Hiroshi Tateishi; Masami Otsuka; Mikako Fujita; Amaç Fatih TuYuN (MDPI AG, 2022)
Colorectal cancer (CRC) and breast cancer are leading causes of death globally, due to significant challenges in detection and management. The late-stage diagnosis and treatment failures require the discovery of potential anticancer agents to achieve a satisfactory therapeutic effect. We have previously reported a series of plastoquinone analogues to understand their cytotoxic profile. Among these derivatives, three of them (AQ-11, AQ-12, and AQ-15) were selected by the National Cancer Institute (NCI) to evaluate their in vitro antiproliferative activity against a panel of 60 human tumor cell lines. AQ-12 exhibited significant antiproliferative activity against HCT-116 CRC and MCF-7 breast cancer cells at a single dose and further five doses. MTT assay was also performed for AQ-12 at different concentrations against these two cells, implying that AQ-12 exerted notable cytotoxicity toward HCT-116 (IC50 = 5.11 ± 2.14 μM) and MCF-7 (IC50 = 6.06 ± 3.09 μM) cells in comparison with cisplatin (IC50 = 23.68 ± 6.81 μM and 19.67 ± 5.94 μM, respectively). This compound also augmented apoptosis in HCT-116 (62.30%) and MCF-7 (64.60%) cells comparable to cisplatin (67.30% and 78.80%, respectively). Molecular docking studies showed that AQ-12 bound to DNA, forming hydrogen bonding through the quinone scaffold. In silico pharmacokinetic determinants indicated that AQ-12 demonstrated drug-likeness with a remarkable pharmacokinetic profile for future mechanistic anti-CRC and anti-breast cancer activity studies.